The Relationship between Self Compassion with Emotional Intelligence of Nurses at Santa Elisabeth Hospital Medan in 2024 - Pakpahan, Rotua E.; Simanullang, Murni Sari Dewi; Zai, Juni Ratna Sari (Mata Pena Madani, 2025)
Emotional intelligence is a person's ability to assess emotions in themselves and others, understand the meaning of emotions and regulate one's emotions regularly in a flow model, therefore emotional intelligence is really needed in nursing services to improve the quality of nursing services. As for social intelligence, it can be influenced by several factors, of which there are internal factors (originating from within the cell) and external factors (from outside the cell, including the environment), other factors can also be seen from the fact that older people may be more likely to be superior in human intelligence illonal. This study aims to analyze the relationship between self-compassion and the emotional intelligence of nurses at Santa Elisabeth Hospital Medan 2024. The type of research design used in this study is correlation design with cross-sectional approach, with a sample size of 132 respondents. The sampling technique in this research is accidental sampling technique. The instrument used is a questionnaire. The results show that the emotional intelligence of nurses in the good category are 23 (23.5%) and sufficient 101 (76.5%). Data analysis used univariate and bivariate with the Spearman rank test. The results of the Spearman rank (rho) statistical test obtained a value of r = (0.248) and p value = 0.004 (p 0.05) which means there is a significant relationship between self-compassion and the emotional intelligence of nurses at Santa Elisabeth Hospital Medan 2024. Based on the results The research described previously proves that self-compassion is closely related to emotional intelligence and has a positive and significant relationship.